The Relationship Between Concentration And Top Serve Accuracy And Bottom Serve In Volleyball - Refalda Herista; Sucipto Sucipto; Ahmad Hamidi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The  game  of Volleyball  is  one  of  the  sports  that  is  widely  taught  in  schools  and developed competitively. One of the basic techniques that plays an important role in  the  game  of  volleyball  is  serve,  which  consists  of  an  upper  serve  and  a  lower serve.  Concentration  is a  psychological  factor  that  is  suspected  to  affect  the accuracy  of  the  serve  because  the  player  must  be  able  to  coordinate  body movements,  regulate  the  power  of  the  shot,  and  direct  the  ball  to  the  target precisely.  This  study  aims  to  determinethe  relationship  between  concentration and the accuracy of the upper serve and the bottom serve in the game of volleyball. This study uses a quantitative descriptive method with a correlational design. The research sample consisted of 15 extracurricular volleyball male athletes of SMAN 10   Bandung   who   were   selected   using   purposive   sampling   techniques.   The instruments used are the Grid Concentration Test (GCT) to measure concentration and  AAHPER  Serving  Accuracy  Test  to  measure  service  accuracy.  The  data  wasanalyzed using the Pearson Product Moment correlation test. The results showed that the relationship between concentration and bottom service accuracy was very low  and  insignificant  (r  =  0.125;  p  =  0.657).  Meanwhile,  the  association  between concentration and   upper   serve   accuracy   showed   a   stronger,   but   also   less statistically  significant  correlation  (r  =  0.480;  p  =  0.070).  The  determination coefficient  (R²  =  0.231)  showed  that  concentration  contributed  23.1%  to  the variation in service accuracy. It was concluded that concentration tends to have a greater role in the upper serve than the lower serve due to its higher complexity of  motion.  However,  no  statistically  significant  relationship  was  found  between concentration and service accuracy in this study sample.